Finite element simulation modeling of axial dynamic energy absorption on conical titanium alloy / Akbar Othman and Al Emran Ismail - Othman, Akbar; Ismail, Al Emran (2012)
This paper presents the finite element simulation of conical unfilled and foam filled titanium alloy subjected to dynamic axial loading. Validation of finite element analysis packages PAM-CRASH 2G version 2005 was compared with existing results from experimental analysis has been done by previous investigation to ensure that the numerical analysis is sufficiently accurate. On the other hand, proper thin-walled titanium alloy as well as polymeric foam material offer vast potential for optimally tailoring a design to meet crashworthiness performance requirements. The energy absorption characteristics of thin-walled alloy and polymeric foam with variable cross-sections in terms of vertex angle and wall-thickness are numerically studied. Results showed that the tube’s energy absorption capability was affected significantly by variations of velocity-impact and wallthickness as well as vertex angle of conical cross-sections. It was also found that as the filling polymeric foam into thin-walled tube increases the amount of absorbed energy than the empty tubes.